PROBLEMATIKA PENEGAKAN HUKUM PERPAJAKAN (KAJIAN TINDAK PIDANA EKONOMI BIDANG MAFIA DAN KORUPSI PERPAJAKAN) - Lamijan Lamijan (UNISSULA, 2014)
More than 60 percent of state revenue derived from the tax sector, but the leak is still very large tax revenues due to the tax mafia and corruption happens everywhere. There are two issues that are discussed in this paper, namely: (1) What are the factors that led to the case of mafia and corruption in taxation difficult to convey? (2) How does the application of policies and formulation of laws that should be done so that the tax mafia and corruption can be eradicated? These two issues are solved using empirical data obtained through the study of documents. The results discussion shows the following findings. That the factors that led to the case of mafia and corruption in taxation difficult to express can be seen from three aspects. First, a substantial aspect, namely the weakness contents of legislation. Most of the legislation that was passed by the government to provide space and opportunities to tax officials for corruption and extortion in order to enrich himself and his colleagues. Second, structural aspects, namely the bureaucratic structure of taxation institutions that do not transparent, thus allowing tax officials do mafia and corruption that tax money should be paid into the state treasury. Tax justice system handledinternally by the institutions have encouraged the proliferation of tax mafia and corruption tax. Third, cultural aspects, namely the lack of honesty in the values of social life.